Submission to the Senate Environment and Communications References Committee Inquiry into Fin-fish Aquaculture in Tasmania - Catriona MacLeod; Donald Ross; Christopher Carter; Caleb Gardner; Marcus Haward; Emily Ogier; Neville Barrett; Christine Crawford; Jeremy Lyle; Jayson Semmens; S Battaglene; Stewart Frusher; et al. (2015)
This submission comprehensively reviews research undertaken by the University of Tasmania’s Institute for Marine and Antarctic Studies (IMAS) and its predecessors, commonly in collaboration with other organisations, over the last 20 years. This research has significantly contributed to knowledge of the environmental impacts and interactions of finfish aquaculture in Tasmania, and provides independent advice and understanding to support decisions regarding the management and regulation of the salmonid farming industry. To date IMAS researchers have played key roles in both identifying and responding to “knowledge gaps” and will continue to do so in the future. Summarised below are the key elements for each term of reference (TOR): (a) the adequacy and availability of data on waterway health: Whether data currently available are adequate depends on the particular issue, as waterway health is a broad term. We focus on the adequacy of data vis-à-vis specific issues as they have arisen; considerable data are available through IMAS. Initially, local scale benthic impacts were the focus, and research was integral to developing management controls. Concern then shifted to broadscale effects of dissolved wastes because research suggested farming in the Huon River/D’Entrecasteaux Channel region was approaching capacity. A limit on further development was imposed, and a Broadscale Environmental Monitoring Program (BEMP) initiated that has since been highlighted as world’s best practice. Concern now focuses on potentially adverse interactions between marine farming and reefs, and on declines in oxygen in Macquarie Harbour. IMAS is currently providing research advice on these issues as part of the adaptive management process. (b) the impact on waterway health, including to threatened and endangered species: Initial research characterised local scale impacts of finfish farms and highlighted that these could be managed within acceptable guidelines. Emphasis then changed to broad scale interactions, and research to date ...